Influence of the application of juvenile hormone on the haemolymph total proteins and electrophoretic pattern of worker larvae of Apis mellifera - Antonialli Jr., Willliam F. [UNESP]; Landim, Carminda C. [UNESP] (My University, 2003)
The aim of the present work was to verify the influence of the juvenile hormone (JH) applied on worker larvae of Apis mellifera 2 to 5 days old over the haemolymph total protein and electrophoretic pattern. Each larvae received topical applications of 1 ml of a solution of JH in hexane (1 μg/ml) on their 2 nd, 3 rd 4 th and 5 th day after hatching and had the amount and electrophoretic pattern of proteins from the haemolymph analyzed during the remaining days of their life. As a control, haemolymph of larvae of the same age that did not receive any kind of treatment was analyzed. The results show that the application of JH on larvae 3 or more days old affect the amount and electrophoretic pattern of the proteins, with this effect lasting through the subsequent days.
Keywords: Apis mellifera; Haemolymph; Juvenile hormone; Proteins